2014
DOI: 10.1242/jeb.094292
|View full text |Cite
|
Sign up to set email alerts
|

Honeybee drones are attracted by groups of consexuals in a walking simulator

Abstract: During the mating season, honeybee males, the drones, gather in congregation areas 10-40 m above ground. When a receptive female, a queen, enters the congregation, drones are attracted to her by queen-produced pheromones and visual cues and attempt to mate with the queen in mid-air. It is still unclear how drones and queens find the congregations. Visual cues on the horizon are most probably used for long-range orientation. For shorter-range orientation, however, attraction by a drone-produced aggregation pher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 50 publications
(71 reference statements)
3
30
0
Order By: Relevance
“…‘during’ phase). Our system was designed to provide clear criteria for measuring whether or not a bee is attracted to an odour and to allow maximal control over experimental conditions 50 . Indeed in the preliminary experiment, appetitively conditioned bees clearly chose to remain in the odour quadrant and walked longer distances in this quadrant compared to control bees (Supplementary Experiment 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…‘during’ phase). Our system was designed to provide clear criteria for measuring whether or not a bee is attracted to an odour and to allow maximal control over experimental conditions 50 . Indeed in the preliminary experiment, appetitively conditioned bees clearly chose to remain in the odour quadrant and walked longer distances in this quadrant compared to control bees (Supplementary Experiment 1).…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the difficulties of testing these ideas in natural mating conditions, research in this direction has little progressed since then. Recently, we tested this hypothesis in the laboratory by using tethered drones freely-walking on an air-suspended trackball 50 . Our study demonstrated that honeybee drones are indeed attracted to the odour bouquet from a group of drones 50 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used a locomotion compensator-based walking simulator similar to other designs (Brandstaetter et al, 2014). It consisted of a Styrofoam sphere (5 cm in diameter, 2.2 g) positioned in a modified plastic funnel and suspended on an air cushion formed by air flowing into the funnel from its neck (Fig.…”
Section: Odor-induced Locomotion In Tethered Honeybeesmentioning
confidence: 99%